Legislating cyberbullying law in Malaysia: a comparative study or analysis to the cyberbullying related law in the United States / Abdullah Munir Roslan …[et al.] - Roslan, Abdullah Munir; Sharudin, Muhamad Arif; Aziz, Muhammad Amin Asyraf; Abd. Khahar, Muhammad Amin Harris (2014)
The purpose of this thesis is to examine the effective ways on curbing the issues of cyber bullying that occurred in Malaysia. Hitherto, the issue of cyber bullying in Malaysia is common, yet the situation is worsen and worrying. Besides, this thesis discusses the inability of the law to control the arising issue. The law such as Computer Crime Act 1997 and Communications and Multimedia Act 1998 list about cyber crimes but there is failure in the enforcement from the public authorities. In addition, comparative study with the United States of America is made as the states in the country have their own legislation specifically regarding cyberbully and can curb such problems. It is hoped that from this research, the country can amend the current laws to provide a specific provision regarding cyberbully and successfully curb the issue.